Polymorphism rs259983 of the ZNF831 gene is associated with the risk of anemia in pregnant women with gestational diabetes - Nataliia Karpova; Olga Dmitrenko; Ekaterina Arshinova; Malik Nurbekov (Egyptian Journal of Medical Human Genetics)
Abstract Background Iron deficiency is a cause of anemia in pregnant women. Iron metabolism is closely related to zinc levels and the state of zinc-containing proteins. Zinc-binding proteins (ZNFs) can also bind other metal ions. Genetic factors can also be a factor leading to unstable iron levels in the blood. Results The aim of this study was to investigate the relationship between rs259983 of the zinc finger protein 831 (ZNF831) gene and anemia in pregnant women with gestational diabetes mellitus (GDM). The PCR test system with Taq-Man samples was developed for genotyping rs259983 of the ZNF831 gene. As a result, an association was found between rs259983 of the ZNF831 gene and the risk of anemia. According to in silico analysis, the ZNF831 protein is able to bind iron (FE, 0.69) and other ions, which may play an essential role in anemia pathogenesis. Conclusions Carriers of the C allele in the homozygous state rs259983 of the ZNF831 are at greater risk of developing anemia. Further studies are required to assess the effect of ZNF831 polymorphisms on the risk of pregnancy pathologies.